"I saw Satan fall like lightning from heaven." Illness as demon possession in the world of the first Christian ascetics and monks - Iosif, Despina (Mental health, religion & culture, 2011)
The late antique world was particularly conscious of malevolent supernatural power constantly laying in wait to attack and enslave humans. Demons incited vices; they could persuade both their unsuspected and suspected victims to venerate them, and to persecute Christians, and to feel an overwhelming attachment to material things. However, what demons seemed to enjoy the most was taking total control by retiring into a human soul. Today our Western civilisation would not easily recognise anti-social behaviour, mental disorder and a strange illness as signs of demon possession, as it was often the case in late antiquity. Christian ascetics and monks were generally considered a very powerful antidote to demonic possession and they managed to enhance their power and to build great reputations, and attract considerable numbers of admirers (even from the upper classes) and converts to Christianity by successfully handling demons.